Connexin 30 deletion exacerbates cochlear senescence and age-related hearing loss - Paciello, Fabiola; Zorzi, Veronica; Raspa, Marcello; Scavizzi, Ferdinando; Grassi, Claudio; Mammano, Fabio; Fetoni, Anna Rita (Frontiers in Cell and Developmental Biology, 2022)
Pathogenic mutations in the Gjb2 and Gjb6 genes, encoding for connexin 26 (Cx26) and connexin 30 (Cx30) respectively, have been linked to the most frequent monogenic hearing impairment, the nonsyndromic hearing loss and deafness DFNB1. It is known that Cx26 plays an important role in auditory development, while the role of Cx30 in hearing remains controversial. Previous studies found that partial deletion of Cx26 can accelerate age-related hearing loss (ARHL), a multifactorial complex disorder, with both environmental and genetic factors contributing to the etiology of the disease. Here, we investigated the role of Cx30 in cochlear aging processes using a transgenic mouse model with total deletion of Cx30 (Cx30  mice), in which Cx30 was removed without perturbing the surrounding sequences. We show that these mice are affected by exacerbated ARHL, with increased morphological cochlear damage, oxidative stress, inflammation and vascular dysfunctions. Collectively, our data demonstrate that Cx30 deletion can be considered a genetic risk factor for ARHL, leading cochlear structures more susceptible to aging processes.